Pengaruh K3 (Keselamatan Kesehatan Kerja) Dan Kepuasan Kerja Terhadap Kinerja Karyawan PT Maxley Bumi Serpong Damai (BSD) Tangerang - Desti Apriliani Puspita Sari; Endang Susilo Wardani (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
PT Maxley BSD bases its business operations on a preliminary survey that shows that employees who are not performing to their full potential in carrying out their responsibilities, as evidenced by poor performance, inability to complete tasks independently, and a low sense of responsibility for the work assigned by the company. This study aims to determine the effect of Occupational Safety and Health (OSH) and job satisfaction on employee performance at PT Maxley Bumi Serpong Damai (BSD), Tangerang. The research was conducted on 50 employees using quantitative methods through questionnaires and multiple linear regression analysis. The results showed that OSH had a 48% influence and job satisfaction had a 43.4% influence on employee performance, while simultaneously both contributed 56.5%. Hypothesis testing with a significance level of < 0.05 proved that there was a significant influence. It was concluded that the implementation of OSH and the improvement of job satisfaction are important to support employee performance, with recommendations for soft skills training and the provision of rewards to increase work motivation.